PP.01.32: TRENDS IN FREQUENCY OF HYPERTENSION IN PATIENTS ADMITTED FOR ACUTE MYOCARDIAL INFARCTION IN SWITZERLAND FROM 1997 TO 2014. (June 2015) - Radovanovic, D.; Bertel, O.; Schoenenberger, A.; Gaspoz, J.M.; Burnier, M.; Erne, P.
Abstract : Objective: There are scarce data available on the temporal trends in preexisting hypertension in patients presenting with acute myocardial infarction (AMI). Design and method: Data were used from the Swiss national registry AMIS Plus (Acute Myocardial Infarction in Switzerland), which prospectively collects data on patients with acute coronary syndrome. All patients with ST-elevation MI (STEMI) and non-STEMI (NSTEMI) enrolled from 1997 to 2014 were included. Trends in the rate of patients with preexisting hypertension were analyzed using multiple logistic regressions. Hypertension was defined if diagnosed and/or treated by a physician. Results: From the 45, 020 patients enrolled for AMI, data on hypertension history was available for 42, 796 (95.1%) patients. Of these patients, 25, 326 (59.2%) had a history of hypertension. The mean age of the total population was 66.1y (SD 13.2y); 66.2y (SD 12.6y) in 1997 and 65.4y (SD 13.0y) in 2014. The percentage of patients with pre-existing hypertension continually increased from 48.7% in 1997 to 63.1% in 2014 (Ptrends < 0.001). This was a 3.5% increase per year (OR 1.035, 95%CI 1.031–1.039; P < 0.001) and 3.7% per year after adjustment for age, gender and type of MI (OR 1.037, 95%CI 1.033–1.041; P < 0.001). The percentage of males with pre-existing hypertension increased in this period of 18 years from 44.6% to 59.5% (Ptrends < 0.001), and in women from 59.3% to 73.4% (Ptrends < 0.001), in STEMI patients from 48.0% to 58.2% (Ptrends < 0.001) and in NSTEMI patients from 50.2% to 71.3% (Ptrends < 0.001). Regular use of angiotensin-converting enzyme inhibitors or angiotensin II receptor antagonists increased from 30.0% to 65.0% (Ptrends < 0.001), beta blockers from 32.6% to 46.6% (Ptrends < 0.001), while no significant changes were found in the regular use of Ca-channel blockers (26.9% to 27.8%; P = 0.61) and diuretics (30.4% to 29.9%; P = 0.063). Conclusions: The number of patients admitted for AMI with pre-existing hypertension constantly increased over the past 18 years in Switzerland. These results indicate that treatment of patients with hypertension appears insufficient and could be improved in order to possibly avoid acute cardiac events.